Fitorremediação de cobre em solo contaminado por rejeito de mineração beneficiado com biochar e composto orgânico - Balbinot, Michele Lusa (2022)
In areas of Cu mining tailings deposits, the concentration of this element occurs, which results in serious environmental problems. Cu is a heavy metal that is not environmentally degradable, accumulating in several environmental compartments. The accumulation of Cu in the soil presents a high potential for toxicity to plants and contamination of the environment, especially in sandy areas, such as those impacted by mining tailings. Phytoremediation is a technique that uses plants to reduce contaminants in the soil. Phytoremediation can be favored by the addition of soil softeners that have the ability to reduce the toxic effect of metals on plants. Biochar is a product that has the potential to immobilize heavy metals, such as Cu, and can be used as a softener. Biochar is a compound rich in C, obtained through the thermal decomposition of biomass, being a product with a bias for the reuse of waste. Another product with potential use as a softener is organic compost, obtained through the composting process. In this context, the objective of the study is to evaluate whether the addition of biochar and organic compost has the ability to reduce the availability and phytotoxicity of Cu in soil from an area impacted by mining tailings and increase the phytoremediation of Cu by Avena strigosa. The experiments were carried out in a greenhouse for the cultivation of Avena strigosa. Soil was collected in an area impacted by Cu mining tailings, in the municipality of Caçapava do Sul/RS. Two softeners were added to the soil, biochar and organic compost. The experiment was carried out in a 2x4 factorial scheme, with 6 replications totaling 48 experimental units. The availability of Cu and other nutrients in the solid phase and in the soil solution, the accumulation of Cu and other nutrients in the shoots and roots, the plant growth and the phytotoxicity of this heavy metal were evaluated. The results showed that the application of compost favored the growth of the plant, which presented a better nutritional status, and increased the phytoremediation power of the plant. In addition, the compost promoted the greatest accumulation of Cu in the plant roots, promoting the phytostabilization process. On the other hand, biochar did not prove to be a good alternative for the cultivation of Avena strigosa, since it was verified a reduction in the growth of the area part and a decrease in the absorption of Cu by the plant. Thus, the addition of organic compost proved to be an efficient strategy to promote the phytoremediation of Cu by Avena strigosa, since it decreased the availability of Cu in the soil and increased plant growth, favoring the absorption of Cu by its tissues, in addition to to reduce the environmental contamination caused by this metal.